DOI: 10.33915/etd.2428
|View full text |Cite
|
Sign up to set email alerts
|

NCAA Division I student athlete characteristics as indicators of academic achievement and graduation from college

Abstract: The purpose of this study was to determine if NCAA Division I student athlete characteristics of graduation, presented in the literature and previous research, can be generalized to student athletes in the Mid-American Conference using research based conclusions developed from this study. The study identified seven characteristics prominent in the literature and made conclusions to ascertain if information provided on the characteristics, as presented in the literature, can be generalized to the Mid-American C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Similar to the current findings, Carter's (2012) examination of student-athlete motivations toward both academics and athletics at a Division I university demonstrated that motivational orientations of athletes differed when accounting for gender. Shuman (2009) also found that female student-athletes were more likely to be academically motivated than male athletes, which was also similar to Simons et al's (1999) and Ridpath's (2002; findings that female studentathletes were better able to balance athletics and academics than male student-athletes.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similar to the current findings, Carter's (2012) examination of student-athlete motivations toward both academics and athletics at a Division I university demonstrated that motivational orientations of athletes differed when accounting for gender. Shuman (2009) also found that female student-athletes were more likely to be academically motivated than male athletes, which was also similar to Simons et al's (1999) and Ridpath's (2002; findings that female studentathletes were better able to balance athletics and academics than male student-athletes.…”
Section: Discussionsupporting
confidence: 55%
“…Some of the aforementioned reforms include the Academic Progress Rate (APR), increased satisfactory progress, and percentage-toward-degree requirements (Meyer, 2005). Academic performance of college athletes in the last ten years has been under a microscope in both the media and the popular literature (Amorose, 2003;Benford, 2007;Meyer, 2005;Pappano, 2012;Ridpath, 2002;. Even with the controversy and challenges, the NCAA touts recent athlete graduation rates of 60%, which is higher than the national average for the nonathletic population at 58% (NCAA, 2002).…”
mentioning
confidence: 99%
“…Previous research examining the relationship between athlete academic success and GPA found variations across sport type and season of competition (Dilley-Knoles et al, 2010). Female athletes were found to have higher grade point averages (LeCrom et al, 2009;Staurowsky et al, 2020), and a coach, athletic department, and institution emphasizing high academic importance influences college athlete academic success (Ridpath, 2002;Tudor & Ridpath, 2018). While the 2.0 standard is the minimum for athletic eligibility, communicating a higher target of 3.0 and connecting students to support services may facilitate more athlete academic success and increase retention.…”
Section: Discussionmentioning
confidence: 99%
“…In the MAC there are 13 member institutions split into an Eastern and Western division with a total student enrollment of more than 275,000, including more than 5,200 athletes in 23 sports (Table 4). Mid-American Conference institutions are considered peers athletically due to competitive equity, number of sports sponsored, athletic budgets, academic profile of prospective college athletes, and many other areas, such as demographics and size of institution (Ridpath, 2002).…”
Section: Demographicsmentioning
confidence: 99%